REKONSTRUKSI ZONASI PENDIDIKAN DASAR DAN LAYANAN INKLUSIF MELALUI TATA KELOLA BERBASIS DATA - Qoriah Rahmawati; Fadlullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Primary school zoning policy has been implemented as a strategy to reduce disparities in educational access through a geographically based approach. However, previous studies indicate that equal access does not automatically lead to educational equity, particularly when school quality, resource distribution, and institutional readiness remain uneven across regions. At the same time, inclusive education emphasizes the importance of addressing the diverse learning needs of students, yet its implementation is often disconnected from zoning policy. This study aims to reconstruct primary education zoning policy through an integrative approach that connects spatial distribution, school capacity, and student needs within a data-driven governance framework. The study employed a conceptual research design using literature synthesis and critical analysis of educational policies. The findings resulted in the development of the Integrated Inclusive Zoning Management Model (IIZMM), which consists of four interconnected components: zoning policy design, inclusive capacity, adaptive school management, and data-driven governance. The study reveals that the main challenge of zoning implementation lies not in the policy concept itself, but in fragmented implementation that fails to integrate access, quality, and inclusion in a systemic manner. The main contribution of this study is the development of a data-driven educational governance model that links equitable access, inclusive education, and quality improvement within a coherent and sustainable framework for primary education.